Response of Holm oak (Quercus ilex subsp. ballota) and mastic shrub (Pistacia lentiscus L.) seedlings to high concentrations of Cd and Tl in the rhizosphere. - Domínguez, María T.; Marañón, Teodoro; Murillo, José Manuel; Redondo-Gómez, Susana (Chemosphere, 2011)
The impairment of root growth and photosynthetical functioning are the main impacts of trace elements on woody plant seedlings. In this work, we assessed the response of Holm oak (Quercusilex subsp. ballota) and mastic shrub (Pistacia lentiscus) seedlings to high concentrations of Cd and Tl in the rhizosphere. These are non-essential trace elements, with a potential high mobility in the soil-plant system. Seedlings of these species are frequently used in the afforestation of degraded soils in mining areas. Plants were exposed to different levels of Cd (20, 80 and 200 mg L(-1)) and Tl (2, 10 and 20 mg L(-1)) in a sand culture. Biomass allocation, growth rates, chlorophyll fluorescence and gas exchange were studied. Both metals affected root biomass. Cadmium produced an increase in the root mass ratio and a decrease in the specific leaf area of the plants in oak seedlings, while Tl did not provoke such response. Mastic plants were more sensitive to Tl and Cd than oak plants. Between elements, Tl provoked more severe toxic effects in the plants, affecting the antennae complexes and reaction centers of the photosystem II. Both elements decreased net assimilation rates (down to a 20% of the control plants) and stomatal conductance (5-10% of the values for the control plants). Cadmium was highly retained in the roots of both species, while Tl was highly translocated into the leaves. In general, Holm oak showed a higher tolerance for Cd than for Tl, and a higher resistance to both metals than mastic shrub, due to a high capacity for Cd retention at the root level. However, such accumulation in roots may induce water stress in the seedling exposed to Cd.
The following values have no corresponding Zotero field: accession-num: 21281955
Keywords: Cadmium Thallium Woody plants Phytostabilization C

Afforestation of a trace-element polluted area in SW Spain: woody plant performance and trace element accumulation - Domínguez, Maria Teresa; Madejón, Paula; Marañón, Teodoro; Murillo, José Manuel (European Journal of Forest Research, 2008)
Trace element soil pollution can have ecotoxic eVects on plants, which could negatively aVect the restoration of a degraded area. In this work, we studied the revegetation success in diVerent sites within a trace elementpolluted area (Guadiamar River Valley, SW Spain). We analysed the survival and growth patterns of aVorested plants of seven Mediterranean woody species, and their relation to soil pollution, over 3 years. We also analysed the trace element accumulation in the leaves of these species. The area was polluted mainly by As, Cd, Cu, Pb and Zn (soil total concentrations up to 250, 3.6, 236, 385 and 510 mg kg ¡1 , respectively). The woody plant performance was very diVerent between sites and between species; in the riparian sites, plant survival rates were nearly 100%, while in the upland terrace sites species such as Quercus ilex and Ceratonia siliqua showed the lowest survival rates (less than 30%) and also the lowest relative growth rates. There were no signiWcant relationships between plant performance and soil pollution in the riparian sites, while in the upland sites mortality, but not growth, was related to soil pollution, although that could be an indirect eVect of diVerent substrate alteration between sites. The accumulation of soil pollutants in the studied plants was low, with the exception of Salicaceae species, which accumulated Cd and Zn in the leaves above 1 and 200 mg kg ¡1 , respectively. We discuss the results with regard to the aVorestation of trace-element polluted areas.
Keywords: Heavy metals; mediterranean woody species; plant survival; relative growth rates; soil remediation

Afforestation of a trace-element polluted area in SW Spain: woody plant performance and trace element accumulation - Domínguez, Maria Teresa; Madejón, Paula; Marañón, Teodoro; Murillo, José Manuel (European Journal of Forest Research, 2008)
Trace element soil pollution can have ecotoxic eVects on plants, which could negatively aVect the restoration of a degraded area. In this work, we studied the revegetation success in diVerent sites within a trace elementpolluted area (Guadiamar River Valley, SW Spain). We analysed the survival and growth patterns of aVorested plants of seven Mediterranean woody species, and their relation to soil pollution, over 3 years. We also analysed the trace element accumulation in the leaves of these species. The area was polluted mainly by As, Cd, Cu, Pb and Zn (soil total concentrations up to 250, 3.6, 236, 385 and 510 mg kg ¡1 , respectively). The woody plant performance was very diVerent between sites and between species; in the riparian sites, plant survival rates were nearly 100%, while in the upland terrace sites species such as Quercus ilex and Ceratonia siliqua showed the lowest survival rates (less than 30%) and also the lowest relative growth rates. There were no signiWcant relationships between plant performance and soil pollution in the riparian sites, while in the upland sites mortality, but not growth, was related to soil pollution, although that could be an indirect eVect of diVerent substrate alteration between sites. The accumulation of soil pollutants in the studied plants was low, with the exception of Salicaceae species, which accumulated Cd and Zn in the leaves above 1 and 200 mg kg ¡1 , respectively. We discuss the results with regard to the aVorestation of trace-element polluted areas.
Keywords: Heavy metals; mediterranean woody species; plant survival; relative growth rates; soil remediation